Electric tractor system propelled by solar energy for small-scale family farming in semiarid regions of the northeast of Brazil - Vogt, Hans Heinrich (2018)
In Brazil, family farming is a significant factor in food production. This applies particularly to the Northeast semiarid regions. However, the majority of semiarid family farms lack appropriate motorized agricultural machinery that provides efficient farming. The hypothesis is that farming equipments developed for those specific climatic and farming conditions will increase productivity of semi-arid family farming. In order to make appropriate farming equipment available for this purpose, the project researched the feasibility of a small-size electric farming tractor, propelled by locally available renewable energy, and capable to pull implements tailored for semiarid family farming. Thus, since onboard availability of sufficient energy is a crucial factor for an electrical vehicle, this project investigated as well alternative systems of power supply, in order to enable the continuous operation of the tractor over longer time periods. The evaluated system included a prototype tractor, besides a scheme for local generation, storage and transmission of electric energy. The obtained result was that, in the semi-arid areas of Brazilian Northeast region, with its reliable and low-cost energy source (photovoltaic), the concept of an electric tractor already represents nowadays an economic and technical feasible solution.